2015
DOI: 10.1007/s00256-015-2139-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical long-term outcome, technical success, and cost analysis of radiofrequency ablation for the treatment of osteoblastomas and spinal osteoid osteomas in comparison to open surgical resection

Abstract: RFA is an efficient method for treating OB and spinal OO and should be regarded as the first-line therapy after interdisciplinary individual case discussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 33 publications
0
60
0
3
Order By: Relevance
“…Radiofrequency ablation has been described as a potentially viable treatment option for spinal osteoblastomas as well, although this has not been widely used universally. 99 Methotrexate has been used as a chemotherapeutic agent within the same context as radiotherapy's use as an adjuvant treatment to surgical intervention. Others have also reported the use of polytherapy with doxorubicin, cisplatin, and methotrexate.…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…Radiofrequency ablation has been described as a potentially viable treatment option for spinal osteoblastomas as well, although this has not been widely used universally. 99 Methotrexate has been used as a chemotherapeutic agent within the same context as radiotherapy's use as an adjuvant treatment to surgical intervention. Others have also reported the use of polytherapy with doxorubicin, cisplatin, and methotrexate.…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…They are typically larger (Ͼ2 cm) and expansile with less sclerotic components compared with osteoid osteomas with thin peripheral sclerosis and may be associated with aneurysmal bone cyst. 43,44 On MR imaging, they demonstrate avid osseous and extraosseous enhancement. Spinal osteoblastomas compose approximately 40% of cases and often involve the posterior elements and are located in the cervical spine in 10%-40% of cases.…”
Section: 34mentioning
confidence: 99%
“…Most untreated lesions lead to painful scoliosis, and surgical excision has traditionally been the treatment of choice for spinal osteoblastomas, which is associated with morbidity, especially given the size of the osseous defect. 43,44 The entire osteolytic component and the soft-tissue component (if present) must be ablated for definitive cure. The imaging guidance (CT) and thermoprotective measures are similar to those in osteoid osteoma ablation.…”
Section: 34mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently published studies indicated promising results, particularly for minimally-invasive treatment of osteoblastoma such that now RFA is currently regarded as the method of choice over surgical treatment [7,32]. Experiences regarding percutaneous thermal ablation of other bone tumors are limited and rely mainly on case reports or small case series, examples of which include the treatment of chondroblastoma [33], eosinophilic granuloma [34] or desmoid tumors [35].…”
Section: Rare Indicationsmentioning
confidence: 99%